2019
DOI: 10.1002/ca.23439
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI activation patterns of cerebellum in patients with epilepsy and brain tumors

Abstract: Function of cerebellum in control and coordination of motor function has been well established for several years. Recent functional magnetic resonance imaging (MRI) studies reveal activation of cerebellum with memory, speech and language tasks. We hypothesize that during every function in the brain signals are relayed to cerebellum. We seek to analyze cognitive, emotional and social functions of cerebellum in patients with brain tumors and epilepsy utilizing functional Magnetic Resonance Imaging. Fifty-one con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…The same principle of precise temporal coordination can here be applied to the phase alignment of neuronal oscillations to optimize coherence and thus cerebral cortical communication in any task dependent manner. Such a role in modulating the communication between cerebral cortical areas would engage the cerebellum in almost any task involving the cerebral cortex and could explain why functional imaging studies reliably detect activation of the cerebellum in a broad range of sensorimotor and cognitive tasks (Zacharia and Eslinger, 2019). Our findings in the cognitive domain and those of others in sensorimotor context strongly suggest the possibility that the cerebellum has a role in coordinating communication through coherence between cerebral cortical areas.…”
Section: Discussionsupporting
confidence: 51%
“…The same principle of precise temporal coordination can here be applied to the phase alignment of neuronal oscillations to optimize coherence and thus cerebral cortical communication in any task dependent manner. Such a role in modulating the communication between cerebral cortical areas would engage the cerebellum in almost any task involving the cerebral cortex and could explain why functional imaging studies reliably detect activation of the cerebellum in a broad range of sensorimotor and cognitive tasks (Zacharia and Eslinger, 2019). Our findings in the cognitive domain and those of others in sensorimotor context strongly suggest the possibility that the cerebellum has a role in coordinating communication through coherence between cerebral cortical areas.…”
Section: Discussionsupporting
confidence: 51%
“… 60–63 Radiological evidence of cross-cerebellar diaschisis, the presence of the pulvinar sign 63 and brain atrophy 64 were indicative of prolonged seizure activity and favoured a particular pattern of seizure spread, including involvement of cortico-ponto-cerebellar pathways. 65 …”
Section: Discussionmentioning
confidence: 99%
“…However, increasing evidence has demonstrated that the cerebellum also plays an important role in cognitive processing, and memory and executive functions are mostly localized in the posterior cerebellum (E et al, 2014), which is supported by many researchers. Functional MRI evidence found cerebellar activation is a consistent finding with memory tasks predominantly in the posterior lobe of the cerebellum (Zacharia and Eslinger, 2019). Schmahmann found that lesions of the posterior lobe of the cerebellum were particularly important in impairments in executive function (Zhuang et al, 2017;Schmahmann, 2019).…”
Section: Discussionmentioning
confidence: 70%